The challenge of determining appropriate care in the era of patient-centered care and rising health care costs. Issue 3 (July 2019) - Coulter, Ian; Herman, Patricia; Ryan, Gery; Hilton, Lara; Hays, Ron D.; ,
Appropriateness of care is typically determined in the United States by evidence on efficacy and safety, combined with the judgments of experts in research and clinical practice, but without consideration of the cost of care or patient preferences. The shift in focus towards patient-centered care calls for consideration of outcomes that are important to patients, accommodation of patient preferences, and incorporation of the costs of care in patient-provider shared clinical decisions. The RAND/UCLA Appropriateness method was designed to determine rates of appropriate or inappropriate care, but the method did not include patient preferences or costs. This essay examines how methods of studying appropriateness can be made more patient-centered by describing a modification of the RAND/UCLA method by including patient outcomes, preferences, and costs.